Exploring cold regions autonomous operations. (August 2021) - Parker, Michael; Quinn, Brian; Bates, Jordan; Hodgdon, Taylor; Bodie, Mark; Shoop, Sally; Stott, Alex
Highlights: SVM's do a good job at classifying the difference between snow and pavement. ROS and Pixhawk controllers together make a good inexpensive vehicle controller. Artificial Intelligence algorithms can be trained from simple vehicle models. Abstract: The US Army must update its vehicle fleet to be better equipped for potential future military conflicts in northern climates (US Army, 2017). This process involves considering manned, optionally manned, and unmanned vehicles as viable options in the future. Optionally manned and unmanned vehicles in the armed forces have substantial benefits because they can operate without direct driver input or are able to perform missions deemed too dangerous for troops. Optionally manned vehicles allow the driver to shift some, or all, focus away from the task of driving the vehicle. In some cases, these autonomous vehicles may perform better than a human driver by rapidly sensing and reacting to terrain changes. Onboard sensing and decision making are equally applicable to both fully autonomous and teleoperated vehicles. This work will focus on the terrain sensing, waypoint navigation, and teleoperation potential of an optionally manned or unmanned vehicle. Results from a vehicle demonstration on two different terrain conditions will provide the basis for additional terrain sensing and autonomous vehicle development work in the coming year.